Declines in highly active antiretroviral therapy initiation at CD4 cell counts ≤ 200 cells/μL and the contribution of diagnosis of HIV at CD4 cell counts ≤ 200 cells/μL in British Columbia, Canada. Issue 6 (27th February 2015) - Lourenço, L; Samji, H; Nohpal, A; Chau, W; Colley, G; Lepik, K; Barrios, R; Lima, V; Hogg, RS; Montaner, JSG; Kesselring, S; Moore, DM
<x xml:space="preserve">Abstract</x> Objectives The aim of the study was to examine trends in initiating highly active antiretroviral therapy (HAART) with a CD4 count ≤ 200 cells/μL and the contribution of having a CD4 count ≤ 200 cells/μL at the time of diagnosis to these trends, in British Columbia (BC), Canada. Methods We included in the analysis treatment‐naïve BC residents aged ≥ 19 years who initiated HAART from 2003 to 2012. Participants were classified as follows: Group 1: diagnosed and initiated HAART with a CD4 count > 200 cells/μL; Group 2: diagnosed with a CD4 count > 200 cells/μL and initiated HAART with a CD4 count ≤ 200 cells/μL; and Group 3: diagnosed and initiated HAART with a CD4 count ≤ 200 cells/μL. We measured trends in initiating HAART with a CD4 count ≤ 200 cells/μL and used logistic regression models to measure factors associated with initiating HAART with a CD4 count ≤ 200 cells/μL, stratified by having a CD4 count ≤ 200 cells/μL or > 200 cells/μL at the time of diagnosis. Results Between 2003 and 2012, 3506 BC residents initiated HAART. Of these, 44% (1558 of 3506) initiated HAART with a CD4 count ≤ 200 cells/μL. This proportion declined from 69% (198 of 287) in 2003 to 21% (81 of 330) in 2012 (P < 0.001). The proportion of those in Group 3 increased from 49% (97 of 198) in 2003 to 69% (56 of 81) in 2012 (P < 0.001). Overall, 56% (1948), 22% (776) and 22% (782) made up Groups 1, 2, and 3, respectively. In adjusted analyses, seeing a specialist was significantly associated with being in Group 3. Using injection drugs and seeing a specialist were associated with being in Group 2. Conclusions In recent years, among individuals who ever initiated HAART in BC, being diagnosed with low CD4 cell counts has become a greater contributor to initiating HAART with low CD4 cell counts.